Ten year longitudinal molecular epidemiology study of Escherichia coli and Klebsiella species bloodstream infections in Oxfordshire, UK - Lipworth, SIW; Vihta, K-D; Chau, K; Barker, L; George, S; Kavanagh, J; Davies, T; Vaughan, A; Andersson, M; Jeffery, K; Oakley, S; Morgan, M; et al. (BioMed Central, 2021)
Background The incidence of Gram-negative bloodstream infections (BSIs), predominantly caused by Escherichia coli and Klebsiella species, continues to increase; however, the causes of this are unclear and effective interventions are therefore hard to design. Methods In this study, we sequenced 3468 unselected isolates over a decade in Oxfordshire (UK) and linked this data to routinely collected electronic healthcare records and mandatory surveillance reports. We annotated genomes for clinically relevant genes, contrasting the distribution of these within and between species, and compared incidence trends over time using stacked negative binomial regression. Results We demonstrate that the observed increases in E. coli incidence were not driven by the success of one or more sequence types (STs); instead, four STs continue to dominate a stable population structure, with no evidence of adaptation to hospital/community settings. Conversely in Klebsiella spp., most infections are caused by sporadic STs with the exception of a local drug-resistant outbreak strain (ST490). Virulence elements are highly structured by ST in E. coli but not Klebsiella spp. where they occur in a diverse spectrum of STs and equally across healthcare and community settings. Most clinically hypervirulent (i.e. community-onset) Klebsiella BSIs have no known acquired virulence loci. Finally, we demonstrate a diverse but largely genus-restricted mobilome with close associations between antimicrobial resistance (AMR) genes and insertion sequences but not typically specific plasmid replicon types, consistent with the dissemination of AMR genes being highly contingent on smaller mobile genetic elements (MGEs). Conclusions Our large genomic study highlights distinct differences in the molecular epidemiology of E. coli and Klebsiella BSIs and suggests that no single specific pathogen genetic factors (e.g. AMR/virulence genes/sequence type) are likely contributing to the increasing incidence of BSI overall, that association with AMR genes in E. coli is a contributor to the increasing number of E. coli BSIs, and that more attention should be given to AMR gene associations with non-plasmid MGEs to try and understand horizontal gene transfer networks.